TINDAK TUTUR EKSPRESIF DAN KOMISIF DALAM DEBAT CALON PRESIDEN REPUBLIK INDONESIA 2014: STUDI ANALISIS WACANA - Juwita, Silvia Ratna (Universitas Esa Unggul, 2017)
AbstractThis research aims to describe and review speech acts in the debate of presidential candidate of the Republic of Indonesia 2014 on June 15, 2014 with the theme of Economic Development and Social Welfare. This research is a qualitative descriptive with content analysis study. The data of this research are (1) expressive speech act in 2014 presidential debate and (2) commissive speech act in 2014 presidential debate. The source of research data is the 2014 presidential candidate debate in the form of speech acts expressed by the 2014 Republican Presidential candidate in the debate. The findings of this research are the speech act illocution in the form of expressive speech acts and commissive speech acts used in every speech of the two presidential candidates at the 2014 presidential debate. This study gives contributions to add insight to the public, and consideration of teachingmaterials for colleges and high schools.Â Keywords: speech act, presidential debate, election Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan dan mengkaji tindak tutur dalam debat calon presiden Republik Indonesia 2014 pada 15 Juni 2014 dengan tema Pembangunan Ekonomi dan Kesejahteraan Sosial. Penelitian ini merupakan deskriptif kualitatif dengan kajian analisis isi. Data penelitian ini adalah (1) tindak tutur ekspresif dalam debat capres 2014 dan (2) tindak tutur komisif dalam debat capres 2014. Sumber data dalam penelitian ini adalah debat calon Presiden Republik 2014 yang berupa tindak tutur yang diungkapkan oleh calon Presiden Republik 2014 dalam debat. Temuan penelitian ini adalah tindak tutur ilokusi berupa tindak tutur ekspresif dan tindak tutur komisif yang digunakan dalam setiap tuturan dari kedua calon presiden pada debat capres 2014. Kegunaan penelitian ini untuk menambah wawasan pada khalayak umum, sebagai pertimbangan materi ajar bagi perguruan tinggi dan sekolah menengah.Â Kata kunci: tindak tutur, debat capres, pemilu